High-performance thin-layer chromatography combined with pattern recognition techniques as tool to distinguish thickening agents. (March 2017) - Ristivojević, Petar; Morlock, Gertrud E.
Abstract: A simple, rapid, and accurate high-performance thin-layer chromatography (HPTLC) method was applied in combination with powerful pattern recognition techniques for differentiating thickening agents, which are mainly based on polysaccharides or biopolymers. After methanolysis, the monomeric units of the thickeners were separated by HPTLC and detected using derivatization with the aniline diphenylamine o -phosphoric acid reagent. According to their resulting fingerprint and chemical pattern, the thickening agents studied have been classified by principal component analysis and by hierarchic cluster analysis in several groups. This newly combined approach using HPTLC fingerprints and pattern recognition techniques differentiated high similarity thickeners. Monomeric units responsible for the classification of the investigated thickener have been identified. The results showed that the HPTLC technique in combination with chemometrics can be a very reliable technique for authentication of high similarity thickening agents and can be used for a quick screening of additives in foodstuffs. Graphical abstract: Highlights: Rapid and reliable classification of different thickening agents. Potential markers identified for distinguishing of thickening agents. Characteristic HPTLC fingerprints of thickening agents analyzed by chemometrics. Planar chromatographic profiling combined with pattern recognition techniques. HPTLC separation and derivatization of the methylated monomeric units.